Activity-dependent synthesis of Emerin gates neuronal plasticity by regulating proteostasis - Yi Xie; Ruoxi Wang; Daniel B. McClatchy; Yuanhui Ma; Jolene Diedrich; Manuel Sanchez-Alavez; Michael Petrascheck; John R. Yates, III; Hollis T. Cline (Cell Reports)
Summary: Neurons dynamically regulate their proteome in response to sensory input, a key process underlying experience-dependent plasticity. We characterized the visual experience-dependent nascent proteome in mice within a brief, defined time window after stimulation using an optimized metabolic labeling approach. Visual experience induced cell-type-specific and age-dependent alterations in the nascent proteome, including proteostasis-related proteins. Emerin is the top activity-induced candidate plasticity protein. Activity-induced neuronal Emerin synthesis is rapid and transcription independent. Emerin broadly inhibits protein synthesis, decreasing translation regulators and synaptic proteins. Decreasing Emerin shifted the dendritic spine population from a predominantly mushroom morphology to filopodia and decreased network connectivity. Blocking visual experience-induced Emerin reduced visually evoked electrophysiological responses and impaired behaviorally assessed visual information processing. Our findings support a proteostatic model in which visual experience-induced Emerin provides a feedforward block on further protein synthesis, refining temporal control of activity-induced plasticity proteins and optimizing visual system function.